The Change in Antioxidant Properties of Dextran‐Coated Redox Active Nanoparticles Due to Synergetic Photoreduction–Oxidation. Issue 36 (16th July 2015) - Barkam, Swetha; Das, Soumen; Saraf, Shashank; McCormack, Rameech; Richardson, David; Atencio, Leonel; Moosavifazel, Vanessa; Seal, Sudipta
Abstract Nanoparticles have proven to be novel material with resourceful applications in the field of nanomedicine. Cerium oxide nanoparticles (CNPs) coated with dextran (Dex–CNPs) have been shown to exhibit anticancer properties which is attributed to the change in oxidation states mediated at the oxygen vacancies on the surface of CNPs. In this study, the extreme sensitivity of Dex–CNPs to visible light is demonstrated using room light with a clear indication of synergetic phenomenon of photoreduction of CNPs in the presence of dextran which undergoes simultaneous oxidation. The phenomenon was further confirmed through a systematic time‐based expedited study using a high intensity visible light source. The physiochemical changes of Dex–CNPs such as dispersion stability, pH, surface chemistry, antioxidant property, cytotoxicity and the surrounding microenvironment of Dex–CNPs were significantly altered on exposure to visible light, thereby affecting the biological response. Given the significance of nanoparticles which are widely researched nanomaterials, in different fields of nanotechnology and biomedicine, this study demonstrates the significant changes in physiochemical properties of Dex–CNPs with light. The photoreduction of Dex–CNPs affects its bifunctional applications in cancer therapy and thereby this study puts forward the necessity to preserve and sustain their properties through proper storage.